2020
DOI: 10.1108/ils-01-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ perception of graduates with on-line degrees in Tanzania: two-pronged lesson for on-line graduates and course developers

Abstract: Purpose This paper aims to explore the employers’ perceptions of graduates with on-line degrees. Design/methodology/approach The Ajzen and Fishbein’s (1980) theory of attitude formation and change informed the study. This Web-based study used self-administered open-ended questionnaires to collect data. It used purposive sampling to select 15 employers from nine employment sectors in Tanzania and used thematic analysis to analyse the data. Findings Findings indicate that employers prefer graduates with trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Literature suggests that some employers use academic qualifications as one of their hiring criteria (Velasco 2012, 13), (Kisanga, 2020). It is interesting to see whether the same applies to this survey's respondents as it might have implications for the RQ 2.…”
Section: Question Rationalementioning
confidence: 77%
“…Literature suggests that some employers use academic qualifications as one of their hiring criteria (Velasco 2012, 13), (Kisanga, 2020). It is interesting to see whether the same applies to this survey's respondents as it might have implications for the RQ 2.…”
Section: Question Rationalementioning
confidence: 77%
“…Due to the distributed geography of students enrolled for online learning, questions around the authenticity and integrity of online assessments remain a topical issue among scholars and practitioners. As a result, some employers often dismiss online education as sub-standard, and often discriminate against holders of online degrees, regardless of how competent they may appear to be [17]. There is a stigma attached to online degrees, one which could disadvantage holders of such qualifications when applying for employment opportunities.…”
Section: Academic Integritymentioning
confidence: 99%
“…On the other hand, institutions that ensure that staff and students act in an integrous manner reinforce their reputation [18], which in turn cultivates confidence in the quality of their online degrees. In a study conducted among employers in Tanzania, Kisanga [17] found that the reputation of the institution awarding a qualification was an important consideration that influenced the hiring decisions of otherwise sceptical employers. Against the foregoing, it is apparent that the enforcement of assessment information integrity is beneficial not only to universities, but to students and graduates as well.…”
Section: Academic Integritymentioning
confidence: 99%
“…Pengguna jasa disini adalah para praktisi yang telah cukup lama bercimpung dan berpengalaman di dunia bisnis atau dunia industri, dan mereka mempekerjakan alumni dari program studi yang sesuai. Dari pengguna jasa, diharapkan diperoleh informasi penting terkait kebutuhan kompetensi lulusan yang relevan, baik kompetensi lunak (softskill) seperti kemampuan kerjasama, komunikasi, interpersonal, maupun keras (hardskill) seperti kemampuan analisis, penyelesaian masalah dan lainnya (Islam & Ahmed, 2015;Kisanga, 2020;Park & Kim, 2022).…”
unclassified